FURFUROL ACETONE EPOXY RESIN CONDENSATION PRODUCT (Scientific journal of the Fergana State University, 2024)
Factors influencing the formation of furfural-acetone monomer FAM in the condensation reaction of furfural with acetone were studied and made it possible to develop an innovative technological process for the production of furan-epoxide binders.